Searching for the Determinants of Climate Change Interest. (30th September 2014) - Cavanagh, Patrick; Lang, Corey; Li, Xinran; Miao, Haoran; Ryder, John David
Abstract : A meaningful CO2 mitigation policy is unlikely at the national level in the United States. What is currently happening and what is much more likely to occur in the future are city and regional level efforts of mitigation and adaptation. This paper aims to understand the geographic and socioeconomic characteristics of metropolitan areas and regions that lead to engagement with the issue of climate change. We use geographically explicit, internet search data from Google to measure information seeking behavior, which we interpret as engagement, attention, and interest. Our spatial Hot Spot analysis creates a map that potentially could be harnessed by policymakers to gauge mitigation support or adaptation potential. The results of our multivariate analysis suggest that socioeconomic factors are the strongest determinants of search behavior and that climate and geography have little to no impact. With regard to political ideology, we find evidence of a nonlinear, inverse-U relationship with maximum search activity occurring in metropolitan areas with a near even political split, suggesting that parity may be good for engagement.